Computational Investigation of the Effect of pH on the Color of Firefly Bioluminescence by DFT - da silva, lp (2011)
In spite of recent advances towards understanding the mechanism of firefly bioluminescence, there is no consensus about which oxyluciferin (OxyLH(2)) species are the red and yellow-green emitters. The crystal structure of Luciola cruciata luciferase (LcLuc) revealed different conformations for the various steps of the bioluminescence reaction, with different degrees of polarity and rigidity of the active-site microenvironment. In this study, these different conformations of luciferase (Luc) are simulated and their effects on the different chemical equilibria of OxyLH(2) are investigated as a function of pH by means of density functional theory with the PBE0 functional. In particular, the thermodynamic properties and the absorption spectra of each species, as well as their relative stabilities in the ground and excited states, were computed in the different conformations of Luc. From the calculations it is possible to derive the acid dissociation and tautomeric constants, and the corresponding distribution diagrams. It is observed that the anionic keto form of OxyLH(2) is both the red and the yellow-green emitter. Consequently, the effect of Luc conformations on the structural and electronic properties of the Keto-(-1) form are studied. Finally, insights into the Luc-catalyzed light-emitting reaction are derived from the calculations. The multicolor bioluminescence can be explained by interactions of the emitter with active-site molecules, the effects of which on light emission are modulated by the internal dielectric constant of the different conformations. These interactions can suffer also from rearrangement due to entry of external solvent and changes in the protonation state of some amino acid residues and adenosine monophosphate (AMP).